Analysis of epidemiologic situation of cholera in 2012 in Kazakhstan - R. S. Musagalieva (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
In the world the tendency of growth of cholera cases has been increasing. In Kazakhstan in 2011 epidemic cholera strains were isolated from the environment. In 2012 the cholera situation was quite stable. The cholera strains were isolated from the environment. Strains V. cholerae non O1 were isolated from people. But all isolated strains were not hazardous. By the complex of factors the South. Kazakhstan. Region is more cholera unfavorable region in Kazakhstan